Stratigraphy and structure of the Punta Negra Anticline. Implications on the structural evolution of the Argentine Precordillera - Alonso, J. L.; Gallastegui, J.; Rodríguez Fernández, L. R.; García-Sansegundo, J. (Journal of Iberian Geology, 2014)
The Punta Negra Anticline is a thrust-related fold, several kilometres wide, located at the front of the Argentine Central Precordillera. A stratigraphic succession including Ordovician, Silurian and Devonian rocks is exposed in its core, instead of a Devonian and Carboniferous succession as previously had been considered. The Punta Negra Anticline also involves a Tertiary sequence displaying syntectonic unconformities in the transition between the Albarracín and Mogna formations, recording the timing of thrusting and folding at the front of the Central Precordillera. This anticline folds thrust systems detached at the Silurian and Devonian shales, which we interpret as pre-Andean (Gondwanan) thrusts in this part of the Precordillera. The pre-Andean age of these thrusts is also consistent with their truncation by Tertiary subvolcanic intrusive bodies that predate the onset of the Andean deformation in the Punta Negra area. Moreover, the size and structural style of the Punta Negra Anticline, Andean in age, is in contrast with the other folds of the Central Precordillera, whose sizes do not exceed the hectometric scale and can be related to Gondwanan thrusting. This implies an Andean deeper thrust, probably detached at the bottom of the Cambrian succession.